Seismic energy theory - Valverde Ramírez, Claudio (2020)
Based on analytical study (in order to establish cause-effect relationship of seismic events) I                     propose the Seismic Energy Theory, according to which a seismic event result of the disturbance of                     the accumulated external energy (solar energy -photons) through the transit of internal energy,                     whose sudden movement -due to the fact that the electrons repel each other- generates seismic waves                     with attenuating and vibratory characteristics, through which there is energy transport in the form                     of vibration without that matter is displaced and is perceived as seismic movements; for such                     eects, the internal energy has a constant path in the form of seismic circuits, in which the                     climate and soil have a determining role.